2021
DOI: 10.1177/03913988211001875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single and multilevel artificial inter-vertebral disc replacement in lumbar spine: A finite element study

Abstract: Degenerative disc disease (DDD) in lumbar spine is one of the major musculoskeletal disorders that cause low back pain (LBP). The intervertebral disc structure and dynamics of the lumbar spine are significantly affected by lumbar DDD, leading to a reduced range of motion (ROM), muscle weakness and gradual degradation. Spinal fusion and inter-vertebral disc replacement prostheses are two major surgical methods used for treating lumbar DDD. The aim of this present study is to examine biomechanical impacts of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To avoid these complications associated with lumbar fusion surgery, artificial disc replacement (ADR) was developed for degenerative lumbar spinal diseases which do not require alignment correction. In a study using finite element analysis, single level ADR showed satisfactory results; however, multilevel ADR showed hypermobility which may lead to alter natural movement of spine and implant failure [ 10 ]. In clinical practice, whether ADR is superior to fusion is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these complications associated with lumbar fusion surgery, artificial disc replacement (ADR) was developed for degenerative lumbar spinal diseases which do not require alignment correction. In a study using finite element analysis, single level ADR showed satisfactory results; however, multilevel ADR showed hypermobility which may lead to alter natural movement of spine and implant failure [ 10 ]. In clinical practice, whether ADR is superior to fusion is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…32 The stiffness of the cage and the match between the cage and the endplate are the major factors need to considered because these parameters play a major role in case of adjacent level disc degeneration. 33 Biswas et al 34 reported that after implantation of single level artificial disc replacement ADR maintains the range of motion closer to natural model and it concludes a low change of disc degeneration after the implant. Rana et al 35 studied posterior dynamic stabilization with flexible rod device and found it is more effective for fusion and maintains the range of motion.…”
Section: Discussionmentioning
confidence: 90%
“…All the seven ligaments were modelled and meshed with the Link 180 element as per the literature. 21…”
Section: Modellingmentioning
confidence: 99%